Modern approach to treatment of a recurrent bacterial vaginosis at women of the reproductive perio - T.Yu.Pestrikova; E.A.Yurasova; A.V.Kotelnikova; N.V. Strelnikova; Yu.V.Voronova; A.V.Chirkov (IP Berlin A.V., 2018)
Bacterial vaginosis is closely associated with increase in frequency of inflammatory diseases of woman's pelvis organs, infertility, spontaneous abortions, preterm labor, contaminating fetus, postnatal inflammatory complications and cervical neoplasia. Goal of the study was to improve treatment of relapsed bacterial vaginosis in women of reproductive age and asses the efficacy of the pathogenetic combination therapy. Materials and methods. In our research we observed 40 female patients, at the age of 18-35 years who were revealed relapsed bacterial vaginosis according to clinical and laboratory examination. We studied their anamnesis, clinical manifistation, microscopic examination of cervical discharge to detect bacterial vaginosis. Also we carried out polymerase chain reaction to identify conditionally pathogenic microbes (Femoflor-16) and pH-metry of vagina contents with colpotest. Results. Our research revealed increased quantity or lack of a normal microflora (Lactobacillus spp.) in all patients. Streptococcus spp. 45.00%; Staphylococcus spp. 40.00%; Atopobium vaginae 80.00%; Gardnerella vaginalis + Prevotella bivia Porphyromonas (titer>106) 70.00% were identified. Combination therapy allows to restore a vaginal ecosystem and prevents bacterial vaginosis relapse over period of 12 months in our patients. Conclusion. Polymerase chain reaction in real time (Femoflor-16) with vaginal pH-metry are the basic laboratory examination methods to confirm bacterial vaginosis. Use of a combination therapy allows to restore a vaginal ecosystem and prevents bacterial vaginosis relapse over period of 12 months in our patients.